Professores-mediadores: contribuições da educação museal na formação e na prática docente - Wellington Luiz Silva (2023)
Mediators of several museums are university students from various courses in a new and important educational experience for their training. These undergraduates take this experience into their training and posterior teaching activities when, later on, they teach in basic education schools. But, what does this museum education experience contribute to teaching practice? This is the question of this research, which focuses on the experience of former undergraduate students who worked as mediators at the Espaço do Conhecimento UFMG and who are currently teachers in basic education, so that understand what are the contributions of their previous experiences in a museum education space for their daily lives in a school. The hypothesis of this work is that the experience with museum education is enriching and deserves to be collected and shared. Through a questionnaire and interviews with these samples, we search for identify didactic approaches and strategies that would have come from these experiences and that these individuals consider especially valuable.As a result of this research, two videos were developed about experiences and challenges in the relationship between museums and schools, which serve as an educational resource for undergraduate and continuing education courses.